The Ohio Supreme Court Sets the Statute of Limitations and Adopts the Discovery Rule for Childhood Sexual Abuse Actions: Now It Is Time for Legislative Action - Yingling, R. Christopher (1995)
This Note discusses the issue of childhood sexual abuse and challenges the appropriateness of Ohio's current statute of limitations for prosecuting a civil claim of childhood sexual abuse. Part II of this Note describes the problem of child sexual abuse in our society. Part III examines the short-and long-term effects of childhood sexual abuse, particularly memory repression. Part IV reviews the theory of recovered memories and the associated problems with reliability. Part V addresses Ohio's governing statute of limitations for civil claims of childhood sexual abuse. Part VI reviews the history of the discovery rule in Ohio and its application to claims of childhood sexual abuse. Part VII examines the function of statute of limitations and proposes a new eight-year statute of limitations for childhood sexual abuse actions in Ohio. Finally, Part VIII concludes that a longer statute of limitations is now more appropriate than the discovery rule because of the reliability problems associated with recovered memories